Menyemai wawasan moderat pada siswa-siswi MAN 1 Kota Kediri melalui seminar moderasi beragama - Anwar, Muhammad Rosihan; Nasrilia, Yonanda Kumala; Awwalina P., Yasmine Azzahra; Khudin, Ahmad Mifta; Virgiawan, Muhammad Raka; Rozaq, Falih Shafiu; Nur Halizah, Khaililla Dara; Ummah, Rachmatul; Ainani’ma, Waffa (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2025)
Community service through the Student Work Course (KKM) at UIN Maulana Malik Ibrahim Malang aims to improve human resources and community welfare. One of the KKM activities is a religious moderation seminar at MAN 1 Kota Kediri on May 4, 2024. This seminar, attended by 30 participants from various student organizations, aims to strengthen the understanding of religious moderation among students to address social and religious challenges. The seminar planning includes selecting speakers, themes, event structure, and target participants. Luthfi Dharmawan, an expert in religious moderation, was the main speaker. The seminar, themed